2020
DOI: 10.1080/15140326.2020.1753468
|View full text |Cite
|
Sign up to set email alerts
|

Can strengthening the local content requirements meet a government’s need to raise industrial productivity and production?

Abstract: By taking firm heterogeneity in productivity into account in a monopolistic competition market in a general-equilibrium model setting, this paper investigates whether a stricter local content requirements (LCRs) can increase both productivity and production in the domestic intermediate-goods industry. The result shows that stricter LCRs policy cannot simultaneously increase both. The initial level of LCRs plays an important role in policy effectiveness. If it is below a critical level, a stricter LCRs can incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The effectiveness of local content requirements in promoting domestic intermediate goods industries has been discussed in the literature. For example, recently, Lin and Weng (2020) have examined theoretically the effect of LCRs on productivity and production in the domestic intermediate-goods industry. They have observed that the effectiveness of this policy depends on the initial level of the local content requirement, given that the LCR cannot increase both production and productivity in the industry.…”
Section: The Restricted Trade Policy Space Can Still Help Promote Dev...mentioning
confidence: 99%
“…The effectiveness of local content requirements in promoting domestic intermediate goods industries has been discussed in the literature. For example, recently, Lin and Weng (2020) have examined theoretically the effect of LCRs on productivity and production in the domestic intermediate-goods industry. They have observed that the effectiveness of this policy depends on the initial level of the local content requirement, given that the LCR cannot increase both production and productivity in the industry.…”
Section: The Restricted Trade Policy Space Can Still Help Promote Dev...mentioning
confidence: 99%
“…Namun niat mewujudkan multiplier effect belum tentu selalu mulus, terutama jika pemerintah tidak memiliki dana untuk pembiayaan proyek sehingga harus berhutang. Sementara di satu sisi terdapat kebijakan dari donor yang mengesampingkan atau membatasi pemanfaatan produk dalam negeri (Lin & Weng, 2020).…”
unclassified